2014
DOI: 10.1007/s00894-014-2125-8
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation on the healing mechanism of divacancy defect in CNT growth by C2H2 and C2H4

Abstract: Experimental studies have shown that chemical vapor decomposition method by using C₂H₂/C₂H₄ as carbon source could dramatically decrease the defects in prepared CNT. However, the inherent mechanism with regards to reduction of defects is quite unclear. In the present paper, density functional theory is used to study the healing process of CNT with divacancy defect by C₂H₂/C₂H₄ molecule. The healing processes undergo three evolution steps: (i) the chemisorption of the first C₂H₂/C₂H₄ molecule on defective CNT; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…[30][31][32] Earlier studies 18,33 have indicated that BNNTs with N-vacancies show a greater chemical stability than those with B-vacancies. Like CNTs [34][35][36] and BNNS, [37][38][39] single vacancy defects in BNNTs can be effectively healed by small molecules, such as NO and N 2 O. 40 Since the energy released during NO or NO 2 chemisorption completely offsets the subsequent barrier, a perfect BNNT can be easily achieved by using NO or NO 2 and defective BNNT as reactants.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Earlier studies 18,33 have indicated that BNNTs with N-vacancies show a greater chemical stability than those with B-vacancies. Like CNTs [34][35][36] and BNNS, [37][38][39] single vacancy defects in BNNTs can be effectively healed by small molecules, such as NO and N 2 O. 40 Since the energy released during NO or NO 2 chemisorption completely offsets the subsequent barrier, a perfect BNNT can be easily achieved by using NO or NO 2 and defective BNNT as reactants.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors also studied the mechanism of healing in carbon nanotubes by ethylene and acetylene, although the details on the preferred orientation of carbon sources on DV were not mentioned. 36…”
Section: Introductionmentioning
confidence: 99%
“…The same authors also studied the mechanism of healing in carbon nanotubes by ethylene and acetylene, although the details on the preferred orientation of carbon sources on DV were not mentioned. 36 Using vdW-DFT calculations, Zhang et al found that the potential energy decreases when acetylene moves from the edge to the center of DV, suggesting that the center of DV is energetically more favourable for acetylene adsorption. Moreover, they reported that acetylene fills DV in graphene with no energy barrier, which is in compliance with previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…For graphene synthesis by CVD the use of both saturated and unsaturated hydrocarbons is essential [5,8,37,38]. Saturated hydrocarbons are stable and less reactive than unsaturated hydrocarbons.…”
Section: Proposed Reaction Mechanismmentioning
confidence: 99%